Improvement of the burning facility of the plant using coal fuel - Sala, Roberto; Alagao, Feliciano B. (2015)
The study is about designing, fabrication and installation of facilities used in improving the burning facility of a plant using coal fuel. The unburned fly ash and coal fines cause adverse impact to the environment and additional overhead expenses to the company. They were briquetted in order to be ready for fuel in the boiler. Facilities for briquetting were designed, constructed, and tested. Main components of facilities are vibrating screen, coal crusher, mixing tank, and agglomeration pan. The binder for briquetting is seaweeds sludge. The result of laboratory analysis of the product with a mixture ratio of 1:0.20 yielded an average stress of 0.023 N/m^2. This strength satisfies the requirement for fuel feed in the boiler.
Keywords: Coal-fired power plants